2015
DOI: 10.4172/1948-593x.1000137
|View full text |Cite
|
Sign up to set email alerts
|

Biofield Treatment: An Effective Strategy for Modulating the Physical and Thermal Properties of O-Nitrophenol, M-Nitrophenol and P-Tertiary Butyl Phenol

Abstract: Phenolic compounds are commonly used for diverse applications such as in pharmaceuticals, chemicals, rubber, dyes and pigments. The objective of present research was to study the impact of Mr. Trivedi's biofield treatment on physical and thermal properties of phenol derivatives such as o-nitrophenol (ONP), m-nitrophenol (MNP) and p-tertiary butyl phenol (TBP). The study was performed in two groups (control and treated). The control and treated compounds were characterized using X-ray diffraction (XRD), differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…As the biofield treated o-and m-nitrophenol had increased the stable isotopic abundance ratio, it might have altered physicochemical and thermal properties and reaction rate. Thus, the current findings are well associated with the previous results [24]. The biofield treated o-and m-nitrophenol might be useful in pharmaceutical and chemical industries as an intermediate for the production of pharmaceuticals and other useful chemicals for the industrial uses.…”
Section: Figure 5 Percent Change In the Isotopic Abundance Ratio Of supporting
confidence: 75%
See 2 more Smart Citations
“…As the biofield treated o-and m-nitrophenol had increased the stable isotopic abundance ratio, it might have altered physicochemical and thermal properties and reaction rate. Thus, the current findings are well associated with the previous results [24]. The biofield treated o-and m-nitrophenol might be useful in pharmaceutical and chemical industries as an intermediate for the production of pharmaceuticals and other useful chemicals for the industrial uses.…”
Section: Figure 5 Percent Change In the Isotopic Abundance Ratio Of supporting
confidence: 75%
“…The gas chromatographymass spectrometry (GC-MS) can perform isotope ratio measurement at low micro molar concentration levels [43][44][45][46]. Recently, it has been reported that Mr. Trivedi's biofield energy treatment (The Trivedi Effect ® ) has the amazing capability to alter the physicochemical and thermal properties of nitrophenol such as crystallite size, particle size and thermal stability that might affect the rate of chemical reaction [24]. Based on all these aspects, the current study was designed to investigate the isotopic abundance ratios of P M+1 /P M and P M+2 /P M in the biofield energy treated o-and mnitrophenol using the GC-MS technique.…”
Section: Ortho-and Meta-nitrophenol (O-and M-nitrophenol)mentioning
confidence: 99%
See 1 more Smart Citation
“…Number of literatures [33][34][35][36] indicated that biofield energy treatment (also known as The Trivedi Effect ® ) might be a potential method for alteration of the isotopic abundance ratio in the organic compounds. An altered physicochemical and thermal properties such as increased crystallite size, enhanced thermal stability was observed in the biofield energy treated PTBP as compared to the control sample through the spectroscopic and thermal study [37]. The toxicity, hazards effects and human health effects by the chemical or material are very closely associated with its intrinsic physicochemical properties [38].…”
Section: Introductionmentioning
confidence: 99%